Guido of Arezzo: between mistake And serendipity (2017)
Few ideas have endured and impacted both the history of Western music and the proposal of Guido de Arezzo in terms of musical notation, close to reaching a thousand years since its initial formulation. This paper contextualizes the contribution of the Arentine monk from a political perspective, within the framework of early Christianity and his search for unitary dogmas. From there a critical observation is raised to their results, relating their intentions to the subsequent development of their ideas; When Guido points out, the characteristics of his system give a boost to the Pythagorean approach to music, which unknowingly configures many of the principles that operate in our musical life today. With that goal in mind, we analyze what Guido did not do and how those shortcomings opened up the possibility of disfiguring his initial purposes.